Age and gender differences in skin characteristics: a study of 2543 Japanese individuals using advanced skin imaging techniques - Yurika Osuji; Jun Omatsu; Shinichi Sato; Ayumi Yoshizaki; Ayumi Yoshizaki (Frontiers Media S.A., 2024)
Skin aging is a multifaceted process influenced by genetic, environmental, and immunological factors, resulting in visible changes such as wrinkles, pigmentation, and alterations in skin texture. Despite its high relevance, there is a paucity of large-scale studies focusing on visible age-related changes in facial skin among Japanese populations, particularly by region. This study aims to address these gaps by examining age- and sex-specific skin changes in a large cohort of 2,543 Japanese subjects using advanced skin imaging techniques. The study included subjects aged 17-71 years who provided informed consent. The imaging system captures facial images using standard light, UV light, and two types of polarized light, applying deep learning techniques to analyze various skin parameters. Statistical analysis was performed to evaluate correlations between age, gender, and skin characteristics. Results indicated significant correlations between age and skin color across all domains, with large pores on the nose showing the highest correlation with age. Sebum and porphyrin levels exhibited a decreasing trend with age, though correlation coefficients were low. Cheek gloss, both in area and color, showed relatively high correlation coefficients. Pigmentation-related items, such as spots and melanin, demonstrated significant age correlations, particularly in areas like the corners of the eyes, under the eyes, and cheeks. Wrinkles and fine wrinkles correlated with age in various regions, though not on the forehead. The findings highlight the importance of understanding regional and demographic variations in skin aging to develop effective anti-aging treatments.